TINDAK UJAR KONVIVIAL DALAM FILM ANOTHER CINDERELLA STORY KARYA DAMON SANTOSTEFANO - CICILIA, SRINITA PUSPA CICILIA PUSPA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This study is an attempt to identify, classify, and describe the category of convivial speech act in the film â€œ Another Cinderella Storyâ€ by Damon Santostefano. In collecting the data, the writer reads relevant books pertaining to convivial speech act, classify the convivial type and analysis speech aspect. In analyzing the data, the writer uses Leechâ€™s concept descriptively based on pragmatic analysis. The findings of the research show that the kinds and the function of the convivial acts in the film â€œ Another Cinderella Storyâ€ by Damon Santostefano are, offering, thanking, greeting, inviting and congratulating.Â  It is excpected that the study will help student and readers in learing pragmatics especially on convivial. Â Â _______________________________________________________________ Keywords : pragmatic analysis; convivial function; speech act;